Targeting the tumor microenvironment with biomaterials for enhanced immunotherapeutic efficacy - Yekai Feng; Qinglai Tang; Bin Wang; Qian Yang; Yuming Zhang; Lanjie Lei; Shisheng Li (Journal of Nanobiotechnology, 2024)
Abstract The tumor microenvironment (TME) is a complex system characterized by low oxygen, low pH, high pressure, and numerous growth factors and protein hydrolases that regulate a wide range of biological behaviors in the tumor and have a profound impact on cancer progression. Immunotherapy is an innovative approach to cancer treatment that activates the immune system, resulting in the spontaneous killing of tumor cells. However, the therapeutic efficacy of these clinically approved cancer immunotherapies (e.g., immune checkpoint blocker (ICB) therapies and chimeric antigen receptor (CAR) T-cell therapies) is far from satisfactory due to the presence of immunosuppressive TMEs created in part by tumor hypoxia, acidity, high levels of reactive oxygen species (ROS), and a dense extracellular matrix (ECM). With continuous advances in materials science and drug-delivery technologies, biomaterials hold considerable potential for targeting the TME. This article reviews the advances in biomaterial-based targeting of the TME to advance our current understanding on the role of biomaterials in enhancing tumor immunity. In addition, the strategies for remodeling the TME offer enticing advantages; however, the represent a double-edged sword. In the process of reshaping the TME, the risk of tumor growth, infiltration, and distant metastasis may increase. Graphical Abstract